Development of an Aspherical Aerial Camera Optical System - Jieqiong Lin; Chenping Jiang; Mingming Lu; Minghui Gao; Qing Guo (IEEE Photonics Journal)
The aerial camera lens largely determines the performance of the camera. It is necessary to further optimize the lens to satisfy the requirements of small-scale and lightweight aircraft camera systems. The optical system design is the primary prerequisite. Therefore, considering the image quality and working environment of the aerial camera, an aspherical aerial camera optical system is developed by studying the aerial camera optical system. The work presented in this paper decreases the overall weight of the aerial camera by using an aspherical lens instead of a spherical lens, which reduces the number of lenses and improves the image quality. The athermalization of the optical system ensures that the camera has good temperature adaptability in the temperature range of −60 °C∼60 °C. The definition of the aspherical surface shape is detected by a ZYGO digital interferometer. The root mean square (RMS) of the system is 0.0403λ(λ = 632 nm), and the peak value (PV) is 0.354λ, which ensures the image quality of the camera. The research results verify that the aspherical lens can be well applied to the camera optical system, improving the image quality of the system and reducing the weight of the camera.